Science, technology, and European cultural heritage : proceedings of the European symposium, Bologna, Italy, 13-16 June 1989 - Baer, Norbert S. (Norbert Sebastian), 1938-; Sabbioni, C.; Sors, A. I. (Andre I.) (Butterworth-Heinemann Publishers, 1991)
Science, Technology and European Cultural Heritage.